Clinical Pharmacogenetics Implementation Consortium Guidelines for CYP2C19 Genotype and Clopidogrel Therapy: 2013 Update - Scott, S A (Nature Publishing Group, 2013)
Cytochrome P450 (CYP)2C19 catalyzes the bioactivation of the antiplatelet prodrug clopidogrel, and CYP2C19 loss-of-function alleles impair formation of active metabolites, resulting in reduced platelet inhibition. In addition, CYP2C19 loss-of-function alleles confer increased risks for serious adverse cardiovascular (CV) events among clopidogrel-treated patients with acute coronary syndromes (ACSs) undergoing percutaneous coronary intervention (PCI). Guideline updates include emphasis on appropriate indication for CYP2C19 genotype–directed antiplatelet therapy, refined recommendations for specific CYP2C19 alleles, and additional evidence from an expanded literature review (updates at http://www.pharmgkb.org).